Analyser la « co-activité didactique » des enseignants du premier degré : l'exemple de l'enseignement de la géographie au cycle 3 - Anne Glaudel (Nantes Université, 2015)
The article deals with teacher's « co-activity », that is to say the part of his activity which is focused on the knowledge items and oriented towards the activity of the pupils with regard to these knowledge items in the framework of greopraghy teaching-learning at primary school. The aim is to understand how the pluri-disciplinary teacher goes through his work when this one consists in setting up situations of knowledge transmission-understanding in a subject that is not his speciality. The didactic analysis leads us to characterise the teaching and learning items, explicitly or implicitly (re)constructed by the teacher. In an inclusive perspective, we mobilise notions from the Clinic of Activity in order to analyse the dynamic process that underlies this (re)construction. From a simple self-analysis interview and from the analysis of the discursive activity of a praticien about his activity in a situation, we introduce the features of a key stage 2 teacher's « didactic co-activity ».